RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays var. saccharata Sturt) DENGAN PEMBERIAN PUPUK LPMKS DAN FUNGI PELARUT PHOSFAT - Parwito, Parwito; Almiyani, Almiyani; Susilo, Edi; Novita, Dian (CROP AGRO, Scientific Journal of Agronomy, 2020)
The purpose of this study was to determine the effect of LPMKS fertiliser and phosphate solubilizing fungi on the growth of sweet corn plants and determine the dose of LPMKS solid organic fertiliser and phosphate solubilizing fungi. This study used a two-factor group randomised design, with the first factor being LPMKS fertiliser and the second factor being phosphate solubilizing fungi. The results showed that the treatment of LPMKS fertiliser did not significantly affect the growth and yield of sweet corn, but there was a tendency that the treatment of 100 g LPMKS produced better growth and yield of sweet corn. The treatment of phosphate solubilizing fungi at a dose of 5 g per plant tended to respond to plant growth and yield. There was an interaction between LPMKS fertiliser and phosphate-solubilizing fungi on the number of cobs parameter. The highest interaction was L3 P1 although not significantly different from L3 P1. The combination of all doses of LPMKS with low doses of phosphate-solubilizing fungi can produce the highest number of cobs.